318 Facilitating mentorship for caregivers of children with atopic dermatitis: the supporting eczema caregivers initiative. (25th January 2023) - Tu, Michelle; Amaro, Lauren; Kidder, Bennett; Kelley, Keri; Capozza, Korey; Schwartz, Alan
Abstract: Caregivers of children with atopic dermatitis (AD) report high levels of stress, feelings of failure and isolation, and a need for social support. These socioemotional effects accumulate over time, often resulting in dramatic changes in career, finances and social activities for caregivers and families when childhood AD is poorly controlled. Psychosocial support and supportive relationships are critical to handling stressful life events. The present study assesses a psychosocial support programme for parents of children with AD. This mentorship program's primary objective was to promote improvements in stress, resilient coping and loneliness among AD caregivers. Participants were randomized to an email-only group ( n = 40) or a one-to-one mentorship pairing ( n = 17). We collected measures of stress, coping resilience, loneliness, AD severity and program satisfaction at baseline, 6 weeks and 12 weeks. Eczema severity significantly decreased overall from baseline to 6 weeks ( P < 0.001) and remained decreased at 12 weeks ( P < 0.001 vs. baseline). There was no significant difference between groups or change in stress, resilience or loneliness over time. Qualitative data demonstrated high program satisfaction. While there was no change in loneliness, resilience or stress, we found a reduction in self-reported eczema symptoms. Continued reduction in these symptoms could affect the overall quality of life, which in turn could yield improved measures of loneliness, resilience and stress.